Empirical Study of Factors Affecting The Value of Telecom Services: Exploring Telecom Services Value Model - Sharma, Kirti (Naše gospodarstvo/Our economy, 2014)
This exploratory study investigated the evolution and changing definition of value proposition in the Indian telecom sector. Mobile phone users who had changed their mobile connection in the recent past were surveyed. The results indicated that, although the price in terms of call and SMS rates was previously regarded as do- minant factors leading to consumer satisfaction, the definition of value has evolved with network connectivity, resulting in followed schemes emerging as the most influ- ential factors. This paper proposes a value model and concludes with a discussion of contributions and proposed ideas for future studies in this area.